Silver nanoparticles by atomic vapour deposition on an alcohol micro-jet - McNally, Michael J; Galinis, Gediminas; Youle, Oliver; Petr, Martin; Prucek, Robert; Machala, Libor; von Haeften, Klaus (Nanoscale advances, 2019)
We achieved sputter deposition of silver atoms onto liquid alcohols by injection of solvents into vacuum via a liquid microjet. Mixing silver atoms into ethanol by this method produced metallic silver nanoparticles. These had a broad, log-normal size distribution, with median size between 3.3 ± 1.4 nm and 2.0 ± 0.7 nm, depending on experiment geometry; and a broad plasmon absorption band centred around 450 nm. We also deposited silver atoms into a solution of colloidal silica nanoparticles, generating silver-decorated silica particles with consistent decoration of almost one silver particle to each silica sphere. The silver-silica mixture showed increased colloidal stability and yield of silver, along with a narrowed size distribution and a narrower plasmon band blue-shifted to 410 nm. Significant methanol loss of 1.65 × 10-7 mol MeOH per g per s from the mature silver-silica solutions suggests we have reproduced known silica supported silver catalysts. The excellent distribution of silver on each silica sphere shows this technique has potential to improve the distribution of catalytically active particles in supported catalysts.